Central Bank of Nigeria : report of the Board Committee on the Banking System - Central Bank of Nigeria (Lagos : Central Bank of Nigeria, 1983)
A report of the Board of Directors of the Central Bank of Nigeria to examine the CBN ACT, unresolved issues in the banking system including privileges granted to licensed banks, to reflect the banking realities in any proposed legislative amendments etc.
opc 30/08/16
Ref
Keywords: Banks and banking. Central; Nigeria